Effective education in home economics development and evaluation of an integrative approach for family life education - Roco, Susana F.
The paper focuses on a crucial area of Home Economics, the Family Life Education (F.L.E) course. The major problem identified is the need to develop and evaluate an integrative affective approach or strategy adequately supported by resource materials, time and space allocations for organized student groups. This paper hopes to help bridge the gap in the teaching-learning system between the objective setting phase and the evaluation phase, help reduce the stigma held for teacher accountability in the attainment of the affective objectives formulated, give more realistic options for the classroom teacher, and serve as a model for the development of other integrative strategies and resources in other crucial areas of Home Economics and related fields.